O81 Development of a mobile application to facilitate in-situ simulation delivery. (5th November 2017) - Edelman, J; Bennett, T
Abstract : Background: Simulation is being used to teach multi professional teams in a range of environments. Moving simulation from the controlled simulation suite to a range of settings including the ward and prehospital environment presents a challenge for educators who need the scenarios at their fingertips to facilitate effectively. With the ongoing development of new simulation material across the world, collating this material becomes challenging and inefficient. It is also recognised that there is currently no simple way of sharing good quality simulation educational material amongst educators. As mobile technology becomes ever more accessible, we present a mobile application which enables simulation material to be collated, shared and delivered from a single device – Simulation Tools And Resources (STAR). Description: Using X code and Swift for iOS, we have developed a mobile app for iOS devices which is available for free on the Apple App Store. The app currently contains a range of locally stored simulation scenarios in a user friendly interface and includes media such as videos, images and sounds. These can be used by healthcare professionals and educators to facilitate simulations in any environment. The application also utilises a server-based back-end, which enables new simulations to be submitted by users and uploaded to the app in real-time, allowing the bank of scenarios to grow and to be easily shared amongst educators. In addition, the application also collates useful weblinks to organisations, moulage tips and other relavent information to enhance simulation delivery. Outcome: The application was released in the Apple App Store in December 2016 and we are currently collecting data on its download and usage worldwide. Feedback on the application has been very positive, and it has already been awarded regional and national awards in the UK. We are currently conducting a pilot study in the South of England to evaluate the impact that our application has on the ease of simulation delivery and the improvement of access to new simulation material. This data analysis will be completed in late 2017. Conclusions: We believe that the STAR application will allow simulation educators to have access to an ever-expanding bank of scenarios which can be delivered with ease in multiple environments. We believe that by embracing a paperless approach to simulation delivery we can improve the way in which in-situ simulation is used and will allow this valuable teaching modality to be utelised more widely. References: . Rosen et al. In situ simulation in continuing education for the health care professions: A systematic review. Journal of Continuing Education in the Health Professions 2012;32(4):243–254. . Eppich et al. Simulation-based team training in healthcare. Sim Healthcare 2011;6:S14–S19.